2014
DOI: 10.4103/1450-1147.138574
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Octreotate Scan in Discrimination of Solitary Pulmonary Nodule

Abstract: Solitary pulmonary nodule (SPN) is one of the most controversial clinical findings in patients. The aim of this study is to use 99mTc-ethylenediamine diacetic acid/hydrazine nicotinamide (HYNIC)-TATE scan technique to evaluate nodules. From 2008 to 2010, 21 patients with SPN underwent 99mTc-HYNIC-TATE scan after the initial assessment with high-resolution computed tomography and then accurate histopathologic diagnosis was established by trans-thoracic needle biopsy, Video Assisted Thoracic Surgery and thoracot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Blum et al [42], in their multicentre trial on a group of 114 patients, concluded that [ 99m Tc]Tc-depreotide showed 96.6% sensitivity and 73.1% specificity in the detection of SPNs. Another radiotracer used in SPNs was 99m Tc-ethylenediamine diacetic acid/hydrazine nicotinamide (HYNIC)-TATE ([ 99m Tc]Tc-HYNIC-TATE), which diagnosed SPNs with a sensitivity of 100% and a specificity of 79% [43].…”
Section: Reviewmentioning
confidence: 99%
“…Blum et al [42], in their multicentre trial on a group of 114 patients, concluded that [ 99m Tc]Tc-depreotide showed 96.6% sensitivity and 73.1% specificity in the detection of SPNs. Another radiotracer used in SPNs was 99m Tc-ethylenediamine diacetic acid/hydrazine nicotinamide (HYNIC)-TATE ([ 99m Tc]Tc-HYNIC-TATE), which diagnosed SPNs with a sensitivity of 100% and a specificity of 79% [43].…”
Section: Reviewmentioning
confidence: 99%